2010
DOI: 10.1021/jm901407s
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in Vitro and in Vivo Biological Evaluation, Docking Studies, and Structure−Activity Relationship (SAR) Discussion of Dipeptidyl Boronic Acid Proteasome Inhibitors Composed of β-Amino Acids

Abstract: A series of novel dipeptidyl boronic acid proteasome inhibitors composed of beta-amino acids were synthesized, in vitro and in vivo biologically evaluated, and theoretically modeled for the first time. From the screened racemic compounds in enzyme, 4i was the most active. The IC(50) value of its pure enantiomer 4q was 9.6 nM, 36-fold more active than its isomer 4p and as active as the marketed bortezomib in inhibiting human 20S proteasome. This candidate also showed good activities with IC(50) values nearly le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 48 publications
(90 reference statements)
2
25
0
Order By: Relevance
“…cently reported. [14,15] In this context, boronic acids 3 c and 3 d showed K i values of 17 and 20 nm, respectively, against ChT-L activity, which are quite comparable to the K i value of bortezomib (9.8 nm), which was tested under the same experimental conditions.…”
Section: Inhibitory Effect On the Cht-l T-l And Pgph Activities Of supporting
confidence: 57%
See 1 more Smart Citation
“…cently reported. [14,15] In this context, boronic acids 3 c and 3 d showed K i values of 17 and 20 nm, respectively, against ChT-L activity, which are quite comparable to the K i value of bortezomib (9.8 nm), which was tested under the same experimental conditions.…”
Section: Inhibitory Effect On the Cht-l T-l And Pgph Activities Of supporting
confidence: 57%
“…Additional structural modifications were the incorporation of different sterically hindered residues at the P2 position, such as phenylalanine in analogy to the structure of bortezomib and b-alanine, taking into consideration that several dipeptidyl boronic acids constructed from b-amino acids are endowed with a good profile in terms of proteasome inhibition, cytotoxic activity versus hematologic tumor cell lines, and pharmacokinetic properties. [14,15] The Leu-boronic electrophilic moiety was maintained as a warhead for its ability to reversibly interact with the N-terminal catalytic active site T1O…”
Section: Introductionmentioning
confidence: 99%
“…These assays provide no information about hidden toxicity or any side effect due to interaction with other molecular targets and cell types and, more importantly, leading to overall toxicity to the whole organism. Recently, in vivo SAR analysis of active compounds that takes bioavailability and ADME (absorption, distribution, metabolism, and excretion) properties of the screened compound into account, has been realized in a zebrafish model []. However, there is no reported study on content screen for both activity and toxicity in zebrafish.…”
Section: Discussionmentioning
confidence: 99%
“…Alongside with physiologic studies synthesis and evaluation of inhibitory activity of its analogues have been carried out. Although in some cases inhibitors of similar potency were obtained (Aubin et al, 2005;Vivier et al, 2005;Zhu et al, 2010) none of them was found to be better than bortezomib.…”
Section: Wwwintechopencommentioning
confidence: 99%